Gender focus in National Agricultural Technology Project (NATP): some issues, - K.UmaRani (Journal of Agricultural Extension Management, 2025)
Innovations in technology dissemination is one of the important components of National Agricultural Technology Project, which lays greater emphasis on the participatory approaches for planning and implementation of strategies. The project envisages gender focus in its strategies to make the extension services more accessible to women farmers. While gender is inherent in the notion of participatory approach, it is often not addressed automatically. One needs to understand that unless concerted and sincere efforts are made to understand and flag the gender issues and thereafter-specific strategies are planned for addressing these issues by integrating them into the project design, no progress can be expected in this regard. This article is an attempt to highlight so’me of the important gender issues in the development process and raise some questions for serious thought and action while planning and implementing Strategic Research and Extension Plans (SREP)